The Effect of Organizational Innovation Through Self-Concept on the Performance of Senior High School Teachers in Kendari City - La Ode Amaluddin; Izlan Sentryo (AL-ISHLAH: Jurnal Pendidikan, 2022)
This study aims to analyze and describe the influence of: Organizational Innovation (IO) through Self-Concept (KD) on teacher performance (KG) at SMAN in Kendari City. Technique Probability Sampling using Proportional Stratified Random Sampling. Data retrieval was carried out using instruments developed by the researchers themselves based on theories built by experts by first being tested on 80 teachers empirically to determine validity and reliability, data analysis techniques were: 1) Analyst prerequisite test, namely normality test, evaluation of univariate outliers and multivariate outliers, evaluation of multicollinearity, evaluation of Goodness-of-fit criteria, reliability and variance extract, 2) Structural Equation Modeling was used to test hypotheses. The results of this study indicate that organizational innovation through self-concept on teacher performance has a positive and significant effect. This finding means that the involvement of organizational innovation through self-concept mediation will improve teacher performance. This is also shown by the results of the indirect effect test (indirect effect) that there is a direct influence of organizational innovation on self-concept of 0.255 and a direct effect of self-concept on teacher performance of 0.260., p-value testing both Sobel test (0.033), Aroian test (0.038), goodman test (0.028), all three are less than the value of = 5%. Based on the three tests, the results of the indirect effect test on organizational innovation through self-concept have a significant effect on teacher performance.